Fenomena Distribusi Zooplankton di Perairan Laut Makassar (Phenomenon of Zooplankton Distribution in Makassar Sea Waters) - Rahmadi Tambaru (Program Studi Manajemen Sumber Daya Perairan, 2018)
The sea waters of Makassar City have oceanographic characters that are influenced by land. The character then influences the distribution of various organisms that live in it. One example is zooplankton. In this study, an analysis of the density distribution of these organisms was carried out to explain phenomena that might be different and not common in marine waters. In fact, the density distribution was found to be highest in locations near the mainland where the highest density was detected in zones 2 and 1 (zone near land). Zooplankton distribution is directly proportional to the level of turbidity in the sea waters of Makassar City.Keywords : Abundance, Zooplankton, Sea, Macassar.